Decision Support System for Solar Energy Adoption - Carlos Lopes; Diogo Martino; Nuno Bandeira; Fernando Almeida (Renewable Energy and Sustainable Development)
A decision support system (DSS) is a computerized information system that combines models and data to solve unstructured or semi-structured problems, with intense user involvement. DSSs have high applicability in several business areas and enable users without technical knowledge in computing to manipulate the information needed for a more assertive decision-making process. This study presents a DSS to support the decision process of installing a photovoltaic solution that considers the contracted power, the monthly expenses in electricity, and the location of the installation. The return on investment is estimated considering the annual savings in electricity and the return on investment. The findings indicate the relevance of the application to support the user in choosing the best solution and reveal that geographical location is a determining factor in the potential energy savings. Furthermore, the payback period decreases by increasing users' monthly consumption and is also potentiated by the increase in contracted power.